Identification of 10 SUMOylation-Related Genes From Yellow Catfish Pelteobagrus fulvidraco, and Their Transcriptional Responses to Carbohydrate Addition in vivo and in vitro - Yang, Shui-Bo; Tan, Xiao-Ying; Zhang, Dian-Guang; Cheng, Jie; Luo, Zhi (Frontiers in Physiology, 2018)
In the present study, we identified ten key genes involved in SUMOylation and deSUMOylation (sumo1, sumo2, sumo3, sae1, uba2, ubc9, pias1, senp1, senp2 and senp3) in yellow catfish Pelteobagrus fulvidraco, investigated their tissue expression patterns and transcriptional responses to carbohydrate addition both in vivo and vitro. All of these members shared similar domains to their orthologous genes of other vertebrates. Their mRNAs were widely expressed in all the tested tissues, but at variable levels. Dietary carbohydrate levels differentially influenced the mRNA levels of these genes in liver, muscle, testis and ovary of yellow catfish. Their mRNA levels in primary hepatocytes were differentially responsive to glucose addition. Our study would contribute to our understanding into the molecular basis of SUMOylation modification and into the potential SUMOylation function in the carbohydrate utilization in fish.